Comparative neutronic study for heterogeneous and homogeneous fuel assembly in a lead-cooled fast reactor. Issue 1 (July 2021) - Ibrahim, Mohammed; Ibrahim, Amr; Aziz, Moustafa; Saudi, H A; Hassaan, M Y
Abstract: ALFRED (Advanced Lead-cooled Fast Reactor European Demonstrator) is a (300 MW th ) pool-type reactor with closed hexagonal Fuel Assemblies (FAs) which are divided into two radial zones (inner and outer core zones). In this work two three dimensional models (3D-heterogenous and 3D-homogeneous) for inner assembly (IA) and outer assembly (OA) have been designed using MCNPX transport code to simulate the neutronic behavior and to study the fuel performance and the effect of homogenization inside the fuel assemblies. The results of the present work for power distribution and fuel burn-up show good agreement between 3D-homogeneous and 3D-heterogeneous models.